The Influence of Digital Marketing Public Relations of Menantea Products on The Purchase Interest of Youtube Users - Muhammad Junaid Kamaruddin; Fauziah Yanis (Journal of Business and Behavioural Entrepreneurship, 2022)
This study aims to find out how much influence PR and MPR have on Menantea's consumer buying interest on Youtube, to find out what is the influence of PR and MPR on buying interest of UEU students, and to analyze whether there is a digital influence of MPR on buying interest of Youtube users. This research is a survey research. The population of this research is youtube users. The sampling method used in this study was accidental sampling with 22 respondents. The collected questionnaire data has been tested using validity and reliability. The data analysis technique in this research is multiple linear regression. The results show that there is a public relationship related to buying interest which is positively influenced by a t-test significance value smaller than the specified significance level, Digital MPR is positively influenced by purchasing decisions with a t-test significant value smaller than the specified significance level and public relations and digital MPR together with buying interest which is positively influenced by the f-test significant value smaller than the specified significance level.